Educational Experience and Political Tolerance: Understanding the Relationship from the Analysis of a Sample of Peruvian University Students - Lars Stojnic Chávez; Andrea Román Alfaro (Revista Internacional de Educación para la Justicia Social, 2016)
The fate of a democracy depends, in part, on the “intrinsic commitment of ordinary people with respect to various democratic principles” (Welzel & Inglehart, 2009, p. 297). This article seeks to identify if having studied more semesters in university would be a factor of influence concerning higher levels of political tolerance or, if rather, the inclusion of a curricular proposal that explicitly addresses contents on citizenship and democracy would have a greater effect. The results indicate that a course oriented to question them about their citizenship exercise would have a positive and significant effect in their levels of political tolerance, as opposed to the number of accumulated academic semesters.